2011
DOI: 10.1152/jn.00287.2010
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor activation enhances inhibitory GABAergic transmission onto hippocampal pyramidal neurons via presynaptic and postsynaptic mechanisms

Abstract: N-methyl-D-aspartate (NMDA) receptors (NMDARs) are implicated in synaptic plasticity and modulation of glutamatergic excitatory transmission. Effect of NMDAR activation on inhibitory GABAergic transmission remains largely unknown. Here, we report that a brief application of NMDA could induce two distinct actions in CA1 pyramidal neurons in mouse hippocampal slices: 1) an inward current attributed to activation of postsynaptic NMDARs; and 2) fast phasic synaptic currents, namely spontaneous inhibitory postsynap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 54 publications
4
40
0
1
Order By: Relevance
“…To decrease the leakage of MK-801 from the recording pipette, the tip was filled with normal intracellular solution and backfilled with MK-801-containg solution, and only low positive pressure was used when approaching the cell. The block of NMDAR activity by intracellular application of MK-801 is a well-established approach and has been used by others before [2,10,30,32] and in our own lab [31]. We observed a significant reduction of the mean sIPSC frequency in WT neurons, whereas NO-GC1KO pyramidal neurons remained completely unaffected.…”
Section: Frequency Of Activity-driven Sipscs Depends On No-gc1supporting
confidence: 53%
“…To decrease the leakage of MK-801 from the recording pipette, the tip was filled with normal intracellular solution and backfilled with MK-801-containg solution, and only low positive pressure was used when approaching the cell. The block of NMDAR activity by intracellular application of MK-801 is a well-established approach and has been used by others before [2,10,30,32] and in our own lab [31]. We observed a significant reduction of the mean sIPSC frequency in WT neurons, whereas NO-GC1KO pyramidal neurons remained completely unaffected.…”
Section: Frequency Of Activity-driven Sipscs Depends On No-gc1supporting
confidence: 53%
“…NMDARs are mostly postsynaptic in the hippocampus (Nyiri et al, 2003;Takumi et al, 1999), and have a greater expression of NR2B subunits than other NMDA subunits (ie, NR2A) in the CA1 subregion, but not in the CA3 subregion or the dentate gyrus (Coultrap et al, 2005;Pandis et al, 2006). Also, within the CA1 subregion, NMDAR subunit composition and density vary across cell types (Angulo et al, 2004;Nyiri et al, 2003;Serrano et al, 2006;Serrano et al, 2008;Siegel et al, 1994;Szabadits et al, 2011;Todd et al, 2006;Xue et al, 2011). Thus, given the functional heterogeneity of hippocampal NMDAR populations (Kesner, 2007;Lee et al, 2003), future studies will be necessary to dissect the role of distinct NR2B subunitcontaining NMDAR subpopulations within the DH in drug context-induced cocaine-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, substantial evidence supporting presynaptic modulation of nigral afferents by both D 1 and CB 1 receptors (Szabo et al 2000;Yanovsky et al 2003;Misgeld et al 2007;Aceves et al 2011) makes inferable that long-term plastic changes may be mediated, modulated, or triggered by these receptors and their associated signaling. Possible mechanisms associated with cannabinergic actions have to be investigated in future studies (e.g., Mulkey et al 1994;Iribe et al 1999;Massey and Bashir 2007;Szabadits et al 2011;Xue et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that AM-251 could not reverse the already installed depression (Fig. 3D, gray bar), suggesting, as the most parsimonious working hypothesis, that this HFS-induced depression is a true long-term depression (LTD) (e.g., Mulkey et al 1994;Gerdeman and Lovinger 2003;Hashimotodani et al 2005;Massey and Bashir 2007;Sergeeva et al 2007;Szabadits et al 2011;Xue et al 2011) in need of further exploration. Because once-established time courses with and without AM-251 were similar, all data were pooled together in the time courses illustrated in Figure 3D.…”
Section: Role Of Cannabinergic Cb 1 Receptors On Striatonigral Synaptmentioning
confidence: 98%
See 1 more Smart Citation